WHAT MOTIVATES INDONESIAN HIGH SCHOOL STUDENTS TO LEARN ENGLISH? - Sri Puji Astuti (Universitas Negeri Padang, 2015)
This multiple case study investigated how teachers implemented motivational teaching strategies and the impact of these strategies on students' motivation in an lndonesian high school context. The participants were four teachers and four groups of their students. The data were collected by conducting semi structure interview for teachers, classroom observation, stimulated recall, and focus group interviews for students. Each teacher had unique strategies to motivate their students and these strategies impacted on students' motivation. The students reported that the strategies influencing their motivation can be categorised into five main groups: teachers' classroom behaviours, supportive classroom atmosphere, selection of learning resources, and activities, the usefulness of English, and the way feedback is given. These findings suggest that teachers of English in an Indonesian high school context can influence their students' motivation by understanding the impact of motivational teaching strategies on students' learning and behaviour.